Peritraumatic reactions in relation to trauma exposure and symptoms of posttraumatic stress in high school students - Nikolas Aho; Marie Proczkowska Björklund; Carl Göran Svedin (European Journal of Psychotraumatology, 2017)
Background: Exposure to traumatic events is clearly associated with a diversity of subsequent mental health problems, with posttraumatic stress disorder (PTSD) as the most prevalent disorder. Epidemiologically, trauma exposure rates are more prevalent than PTSD, indicating that most trauma victims do not develop PTSD. More knowledge is needed to understand the development of the different posttraumatic pathways including the significance of pretraumatic, peritraumatic and posttraumatic risk factors. Objective: To study peritraumatic reactions in relation to trauma exposure and symptoms of posttraumatic stress and to enhance our understanding of peritraumatic reactions as mediators between trauma and later symptomatology. Method: The study was composed of a representative community sample of 5332 second year high school students (mean age 17.3 years) who completed the Juvenile Victimization Questionnaire (SAQ/JVQ), Trauma Symptom Checklist for Children (TSCC) and answered questions about peritraumatic reactions. Mediation effects of peritraumatic reactions on the trauma exposure relationship to symptoms was tested using the PROCESS macro for SPSS. Results: Traumatic events are common (84.1%) and are accompanied in three-quarters of the students with at least one form of peritraumatic reaction. Peritraumatic reactions, especially peritraumatic dissociative reactions, mediate the relationship between trauma exposure and symptoms, and gender moderates the effect of peritraumatic dissociation. This moderating effect was found to be larger for boys than for girls, indicating gender differences in response to trauma. Conclusions: The results indicate the need to screen for peritraumatic reactions as early as possible after a traumatic event in order to identify those at risk for PTSD.